Control of Lymphorrhea and Treatment of Warty Excrescences in Elephantiasis - José Maria Pereira de Godoy; Patricia Amador Franco Brigídio; Edivandra Buzato; Maria de Fátima Guerreiro Godoy (Case Reports in Dermatological Medicine)
The aim of this study is to report the control of lymphorrhea in the intensive treatment of elephantiasis, using an Unna boot. The case of a 29-year-old female patient is reported. This young patient evolved with the more serious form of lymphedema, elephantiasis, after surgical treatment of an abdominal neoplasm and radiotherapy. Warty excrescences were present on both legs and genitalia where lymphorrhea was constant. The patient arrived at the Godoy's Clinic for treatment. She was weighed and perimetric evaluations were made at the start of treatment and thereafter every day during an intensive outpatient treatment of eight hours daily for three weeks. Treatment included manual lymph drainage, mechanical lymph drainage using the RA Godoy device, and the continuous use of compression stockings with adjustments made every three hours. An Unna boot was employed as compression at sites of dermal lesions (warty excrescences) with overlapping use of individualized compression stockings that were individually adapted. The Unna boot was renewed every two days during the first week and every 3 days during the second and third weeks. By the end of this course of treatment, most of the warty excrescences had reduced in size or even disappeared and the lymphorrhea was controlled.